DEVELOPING FINE MOTOR SKILL USING MODEL PROJECT BASED LEARNING, DEMONSTRATION METHODS AND ORIGAMI PAPER MEDIA AT ADHYAKSA XIV KINDERGARTEN - Khairah, Ikrima; Sari, Dessy Dwitalia (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2024)
The Problems is several children show the coordination delays through the lack of student ability in developing imagination by using paper folding, cutting, and sticking picture techniques in activities. The solution provided is to use task-based learning, demonstration methods and origami paper media. The purpose of this study was to describe teacher activities, children's activities, and the results of fine motor development through origami paper folding activities. The exploration approach uses subjective research methodology with the type of homeroom teacher activity research directed by 4 cycles, the research setting was carried out on class B children of Adhyaksa XIV Kindergarten Banjarmasin totaling 15 children consisting of 6 boys and 9 girls. The type of data uses qualitative data. Data analysis was carried out descriptively qualitatively with observation sheets and rubrics. The results of the examination showed that (1) the movement of instructors in groups 1 to 4 increased to a level of 100% of the